Parapleisticantha Yokoya, 1933, a valid genus of deep-sea inachid spider crab from Japan and the Philippines (Crustacea: Decapoda: Brachyura: Majoidea), with the description of a new species - de Forges, Bertrand Richer; Ng, Peter K.l.; Ahyong, Shane T. (Zootaxa, 2013)
The inachid spider crab genus, Parapleisticantha Yokoya, 1933 [type species: Parapleisticantha japonica Yokoya, 1933] is removed from the synonymy of Pleistacantha Miers, 1879 [type species: Pleistacantha sanctijohannis Miers, 1879], and recognised as a valid genus. Parapleisticantha differs from Pleistacantha sensu stricto primarily by having a less spiny carapace, stouter and more inflated male chelipeds, and by lacking a slender subdistal process on the male first gonopod. We redescribe Parapleisticantha japonica based on the Japanese type material and describe as new a second species, Parapleisticantha ludivinae n. sp., recently discovered in thePhilippines.